Chemistry - Grechanyuk, V.; Kozyrev, A.; Grechanyuk, I.; Matsenko, O.; Vitovetska, T.; Chornovol, V.; Kovalchuk, Y. (KNUCA, 2024)
Contains the main theoretical material in general and inorganic chemistry within the discipline for applicant of higher education in construction and related specialties, including the manufacturing of materials. Contains test questions for self-work. Intended for applicant of higher education of specialties 192 "Construction and civil engineering" and 161 "Chemical technologies and engineering". Містить основний теоретичний матеріал із загальної та неорганічної хімії в межах дисципліни для здобувачів вищої освіти будівельних та споріднених спеціальностей, зокрема виробництва матеріалів. Містить контрольні запитання для самостійної роботи. Призначено для здобувачів вищої освіти спеціальностей 192 «Будівництво та цивільна інженерія» та 161 «Хімічні технології та інженерія».
Хімія
Keywords: chemistry; хімія; неорганічна хімія; 54(075.8)